1995
DOI: 10.1091/mbc.6.7.929
|View full text |Cite
|
Sign up to set email alerts
|

Insolubility and redistribution of GPI-anchored proteins at the cell surface after detergent treatment.

Abstract: A diverse set of cell surface eukaryotic proteins including receptors, enzymes, and adhesion molecules have a glycosylphosphoinositol-lipid (GPI) modification at the carboxy-terminal end that serves as their sole means of membrane anchoring. These GPIanchored proteins are poorly solubilized in nonionic detergent such as Triton X-100. In addition these detergent-insoluble complexes from plasma membranes are significantly enriched in several cytoplasmic proteins including nonreceptor-type tyrosine kinases and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
204
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(220 citation statements)
references
References 60 publications
(109 reference statements)
15
204
0
1
Order By: Relevance
“…However, most data indicate that antibody binding and cross-linking do not disrupt (our unpublished results) (Mayor and Maxfield, 1995;Kenworthy and Edidin, 1998) and indeed may stabilize (Harder et al, 1998) the association of proteins with lipid rafts. The great exception is the observation that clustering of folate receptor is disrupted by binding of the antibody MOv19 (Smart et al, 1996).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…However, most data indicate that antibody binding and cross-linking do not disrupt (our unpublished results) (Mayor and Maxfield, 1995;Kenworthy and Edidin, 1998) and indeed may stabilize (Harder et al, 1998) the association of proteins with lipid rafts. The great exception is the observation that clustering of folate receptor is disrupted by binding of the antibody MOv19 (Smart et al, 1996).…”
Section: Discussionmentioning
confidence: 71%
“…We confirmed this in HeLa cells by incubating labeled cells in PBS containing 1% Triton X-100 for 30 min on ice and then fixing the cells and visualizing the detergent-insoluble membrane fraction by fluorescence microscopy (Mayor and Maxfield, 1995;Kenworthy and Edidin, 1998). As expected, CTXB, folate receptor, and CD59 all were present after detergent extraction at levels similar to that of mock-extracted cells, whereas transferrin receptor labeled with fluorescently tagged human transferrin was completely extracted under these conditions (our unpublished results).…”
Section: Fret Microscopy Of Lipid Raft Componentsmentioning
confidence: 73%
“…Hence, separate detergent-resistant domains exist in those cells, but they are indistinguishable by the DRM criterion. Detergent treatment leads to coalescence of detergent-resistant cholesterol-sphingolipid micodomains, which come together to form aggregates or fuse into continuous membrane sheets (27,28). It has also been demonstrated that detergent intercalation into model membranes can promote the formation of DRMs (29).…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation of gradient centrifugation experiments remains controversial. There is evidence that detergents may force associations between components that are not colocalized in intact cells (Mayor and Maxfield, 1995), and fractionation results are known to be dramatically altered by varying the concentration of Triton X-100 (Field et al, 1999;Parolini et al, 1999), by use of alternative detergents (Montixi et al, 1998;Surviladze et al, 1998) or by omission of detergent altogether (Ilangumaran et al., 1999;Harder and Kuhn, 2000;Surviladze et al, 2001). Methods to observe membrane segregation in situ have also generated controversy.…”
Section: Introductionmentioning
confidence: 99%